The influence of the sinonasal microbiome on the development and management of rhinosinusitis - Miriam Lang; Dawid Bereza; Maria Kulak-Waśniewska; Igor Moreau; Paulina Polańska; Katarzyna Sokołowska; Barbara Woch (Journal of Education, Health and Sport)
Introduction and purpose: Chronic rhinosinusitis (CRS) is a frequently diagnosed condition in patients seeking medical care. It encompasses a range of disorders that can be classified based on underlying causes, clinical symptoms, or inflammatory types. Although the precise cause of CRS remains unclear, the European Position Paper on Rhinosinusitis and Nasal Polyps 2020 (EPOS 2020) has recently offered updated insights, treatment strategies, and recommendations.